ANALISIS PENGARUH KUALITAS PELAYANAN SAMSAT BANDAR LAMPUNG TERHADAP KEPUASAN WAJIB PAJAK - Bursan, Rinaldi; Chanerie, Dhaniel J (Jurnal Manajemen dan Keuangan, 2012)
Samsat (Sistem Pelayanan Satu Atap) Office Bandar Lampung is one of the government agencies that provide services to the public /community relating to the payment of taxes on motor vehicles. Samsat Office Bandar Lampung serve the average number BBNKB for two-wheeled vehicles as much as 5057 units per month. While the number of people who renew PKB to launch an average of 8959 vehicles per month. For the average car as much as 442 per month for the renew of BBNKB and 4289 for payment of PKB. The independent variable of responsiveness is the most influential variable with a regression coefficient of 0.446 and a further variable respectively are under the influence of the independent variables to the regression coefficient guarantees for 0.373, the physical appearance of the independent variables with the regression coefficient of 0.237, the independent variable of empathy with the regression coefficient of 0.203 and the independent variables to the regression coefficient reliability of 0.129 who expressed a positive effect on the quality of services to the satisfaction of the community can be accepted.Keywords :Quality of Service, Taxpayer Satisfaction